(untitled) (Indian Journal of Public Health Research & Development, 2020)
The loss of bonding attachments to maternal deaths as a cause of neonatal stress had an impact on brain growth and development in early life. HPA axis activation responsed to secrete corticotropin releasing hormone which stimulated adrenocorticotropic hormonessecretion. These hormones induced the adrenal gland cortex to secrete glucocorticoids. Excessive release of glucocorticoids would suppress BDNF expression resulting in BDNF hypofunction resulting in neuronal cell apoptosis which was characterized by an increase in neuronal cell apoptosis index. This study aimed to analyze the apoptosis index of neuron cells in the cerebrum and cerebellum of newborn Rattus norvegicus that were not separated from the mother until 3 days old as the control group (K1) and the cerebrum and cerebellum of newborn Rattus norvegicus that were separated from the mother by giving animal milk as replacement nutrition until 3 days old as a group treatment (K2). 3 Rattus norvegicus newborn with heaviest, medium, and lowest weights were taken from each mother then sacrificed for the brain histochemical preparations. Imonohistochemical examination was carried out to calculate the neuronal apoptosis index. The analysis results showed that the apoptotic index of neuron cells in the cerebellum and cerebellum of newborn Rattus norvegicus which separated from the mother were higher than those not separated from the mother.